Job shop conversion of manufacturing system to cellular manufacturing - Hamza, Sanaa Ali (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Recently, the Cellular Manufacturing (CM) which is based on the Group Technology (GT) principles is seen to be the alternative system to handle the challenges for the global manufacturing systems. The main objective of the current research is to develop a tool for integrating the Feasibility Assessment (FA) with the Cell Formation (CF). This tool aims to prevent the failure after applying the CM. To get the benefits of this tool, firstly a Similarity Coefficient (SC) based method was proposed to complete the work in the FA stage, and then another SC based method was developed to complete the work in the CF stage, afterward; the two methods integrated together by using two assumptions and the same SC measure. The developed tool performs better than the previous well-known SC based methods when tested, using nine performance measures selected from literature. Also, it can apply smoothly in the job shop based factories.The significant of the developed tool is that, the factories can use this tool as a decision support tool to test the existing data before applying the Cellular Manufacturing System (CMS). In addition the factories can control on the conversion process from evaluation the data to application of the CMS. The main question of the problem statement is how to integrate the FA into CF. Next how to solve all the questions related to complete the integration process. The main objectives to solve the problem statement are: to propose a method for FA, to develop a method for CF and to integrate between these two methods. The methodology that followed to achieve the objectives is as follows: firstly a method based on SC measures was applied to identify (the decision of applying the CM, the predicted number of machine cells and the quality of the solution) in the FA stage. Secondly, another method also based on using SC was developed to create machine cells and part families in the CF. Then these two methods were integrated together, using two assumptions and the same SC measure in both stages the FA and CF. For validating work, the developed tool applied in three factories located in Malaysia and Iraq. For more validation the results of the developed tool compare with the results of some well-known methods known as Agglomerative Hierarchical Clustering (AHC). The results prove that the developed tool perform better than the previous AHC methods and leads to increase the grouping efficacy, reduce the intercellular moves and saved the material handling cost. Through the current research new performance measure called integrated index was developed to integrate the quality of the solution in the FA and CF. Moreover, for the same purpose, new mathematical model solved, using Genetic Algorithm (GA) was developed. The contribution to knowledge for this research is the developing of tool, mathematical model and index for integrating the FA and CF. For the future work, it is suggested to use part attribute matrix, other SC measures based on real life production features and other design stages such as cell layout, cell schedule to integrate with the FA.